PERAN CAMAT DALAM PENGELOLAAN ADMINISTRASI PEMERINTAH DESA DI KECAMATAN TUMPAAN KABUPATEN MINASAHA SELATAN - LAMIA, GLENTIO FALEN; Laloma, Alden; Pombengi, Jericho (Sam Ratulangi University, 2015)
ABSTRAK : This study aims to identify the role of Head Tumpaan in carrying out its duties andfunctions are actually especially in managing the administration in villages in districts Tumpaan.In thisresearch using descriptive qualitative method, with the informant as many as 14 people were taken from therelated elements, namely sub-district, sub-district secretary, the village head, village secretary, members ofthe Village Consultative Body (BPD), and leaders / members of the public. And this study also taken fromthree villages in the district Tumpaan, 3 village in select from the closest distance, middle, and furthest fromthe central district.In this study it can be concluded that the role of the Head in carrying out duties and functionsespecially in managing administration in the village in the District Tumpaan can not say maximal, the articleinformant argued there is less satisfactory in performance Head. It can be recommended suggestion thatthere should be more efforts to Head saw no hope for the people in the fight for the government, especially inthe sub-district administration.Keywords: Duties and functions Head to the village.PENDAHULUANDalam penyelenggaraan pemerintahandaerah, UUD